Evaluating the Dynamics of Energy Economics in the Pursuit of Sustainable Development - Ali, Bashar Mahmood; Ahmed, Ahmed Omer; Abedah, Maher; AbdulRahman, Mujahed Mutlaq (Journal of Ecohumanism, 2024)
Background: The pursuit of sustainable development globally has brought energy economics to the forefront. The intricate interplay between energy production, consumption, and economic growth demands an in-depth comprehension of their interrelationships. This research delves into the intricate association of energy economics with sustainable development, considering the complexities arising from balancing economic progress with environmental preservation.Objective: This research aims to evaluate the correlation between energy economics and sustainable development through the study of diverse energy sources. The economic feasibility and environmental impact of these sources will be assessed, and their policy implications will be evaluated. Our primary objective is to identify strategies that promote the alignment of energy economics with long-term development objectives. Methods: In this study, a multidisciplinary approach is employed, which combines quantitative analysis, econometric modeling, and policy evaluations. A comprehensive analytical framework is developed with data from different sources, including environmental impact assessments, consumption patterns, energy production, and economic indicators. Results: The research reveals the complex link between energy economics and sustainable development. It presents the difficulties in shifting to renewable energy sources while still ensuring economic growth, explains the effectiveness of policy interventions, and underscores the need to balance short-term economic gains against long-term environmental sustainability. Conclusion: The research highlights the significance of harmonizing energy economics with sustainable development objectives. A uniform policy structure that promotes the adoption of renewable energy, while assessing social and economic aspects, is of crucial importance. A collaborative approach from policymakers, businesses, and society is necessary to realize a sustainable energy future.